Does green vertical farming offer a sustainable alternative to conventional methods of production?: A case study from Scotland - Frances Sandison; Jagadeesh Yeluripati; Derek Stewart (Food and Energy Security, 2023)
Abstract Climate change is an existential global reality that is placing considerable stress on agriculture sectors. With the recognition of the impacts of climate change on food security, there has been a greater uptake of controlled environment agriculture (CEA) to provide climate‐resilient and high‐quality production. Vertical farming (VF) can allow primary production in urban locations as well as reducing seasonality and variability in produce. It is emerging as an alternative to traditional farming methods. This research aimed to explore the major environmental impacts of VF produce in comparison with conventional farming methods, using lettuce as an example crop. Life cycle analysis indicate that electricity consumption by VF account for 91% of the carbon footprint. Under the 2019 Scottish electricity mix, VF did not offer a viable competitor for UK open‐farmed lettuce or Spanish imports in terms of low greenhouse gas emissions (at approximately 1.49 kgCO2 eq. kg−1). However, with increasing use of renewable electricity in the national mix, by 2020, this had dropped to 0.42 kgCO2 eq. kg−1 making it comparable with UK open‐field agriculture (at approximately 0.46 kgCO2 eq. kg−1). Under a 100% renewable electricity generation scenario, VF‐related emissions drop further (to 0.33 kgCO2 eq. kg−1). This would potentially offer a low‐carbon production method not subject to seasonality which is better than that reported by most other production methods and offers higher water and nutrient efficiency. This research highlights green VF as potential alternative for sustainable future produce especially under changing climate scenarios.